Nanocrystalline TiO(2) Sensitive Layer for Plasmonic Hydrogen Sensing - Gazzola, Enrico (Nanomaterials (Basel), 2020)
Solution processed TiO(2) anatase film was used as sensitive layer for H(2) detection for two plasmonic sensor configurations: A grating-coupled surface plasmon resonance sensor and a localized surface plasmon resonance sensor with gold nanoparticles. The main purpose of this paper is to elucidate the different H(2) response observed for the two types of sensors which can be explained considering the hydrogen dissociation taking place on TiO(2) at high temperature and the photocatalytic activity of the gold nanoparticles.